Peritumoural adipose tissue pro‐inflammatory cytokines are associated with tumoural growth factors in cancer cachexia patients. Issue 6 (3rd October 2018) - Neto, Nelson Inácio Pinto; Murari, Ariene Soares de Pinho; Oyama, Lila Missae; Otoch, José Pinhata; Alcântara, Paulo Sérgio Martins; Tokeshi, Flavio; Figuerêdo, Raquel Galvão; Alves, Michele Joana; Lima, Joanna Darck Carola Correia; Matos‐Neto, Emídio Marques de; Seelaender, Marilia; Oller do Nascimento, Claudia Maria
Abstract: Background: Cancer cachexia (CC) is a multifactorial syndrome, often irreversible, that affects patients with cancer influenced, in part, by the inflammatory condition. Peritumoural adipose tissue produces adipokines and angiogenic, apoptotic, and growth factors; given the possible crosstalk between the peritumoural adipose tissue and tumour, these may play an important role in cancer biology and carcinogenesis. Methods: The aim of this study was to evaluate the factors produced by peritumoural adipose tissue in a cohort of 16 colorectal cancer patients with either weight‐stable cancer (WSC; n = 7) or CC ( n = 9). The study was approved by the Ethics Research Committee (972.914). Samples of peritumoural adipose tissue were analysed for concentrations of TNF‐α, IL‐1β, STAT‐1, STAT‐3, RANTES, IL‐1Ra, IP‐10, IL‐15, MCP‐1, IFN‐α, GCSF, FADD, and TGF‐β. The cytokines and proteins were measured using Multiplex. Correlations between the proteins and cytokines were evaluated. Results: TNF‐α, STAT‐1, and FADD, a factor involved in apoptosis, were significantly higher in CC group than in the WSC group. In the peritumoural adipose tissue of the CC group, RANTES showed a significant positive correlation with IL‐1Ra and IP‐10 and a negative correlation with IFN‐α; and GCSF showed significant negative correlations with IL‐1Ra, IP‐10, IL‐15, and MCP‐1 and a positive correlation with IFN‐α. In the peritumoural adipose tissue of the WSC group, no significant correlations were detected between RANTES, GCSF, IL‐3, FADD, and STAT‐1 and the cytokines/chemokines analysed. Conclusions: These results indicated that inflammatory and tumorigenic pathways were altered in peritumoural adipose tissue in CC. Furthermore, inflammatory cytokines were correlated with growth factors in the peritumoural adipose tissue of cachectic patients, suggesting that inflammatory cytokines modulated the proliferative environment closely linked to the tumour.